Localización óptima de viveros ornamentales con Sistemas de Información Geográfica (SIG) en la ciudad de Bogotá, Colombia - Guzman Zabala, Juan Francisco
This work aims to examine the spatial distribution of the supply for ornamental plants and their potential demand in Bogotá (Colombia) through geomarketing, in order to identify underserved areas for the location of new ornamental nurseries. For this purpose, Geographic Information Systems (GIS) are used, specifically the kernel density method, to represent the variables of interest (supply and demand) as densities. In the offer, the ornamental nurseries registered with the Colombian Agricultural Institute (ICA) are analyzed. In the demand the properties are analyzed, differentiated in three strata according to their socioeconomic level (4, 5 and 6). The application of these techniques allowed to identify 19 neighborhoods, underserved areas, with a potential market of 12,134 families, estimating annual income for the new point of sale of approximately $ 354 645 213 MCTE.